Öffentliches Recht und Privatrecht - Sacksofsky, Ute (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2020)
This conference volume presents lectures and discussion from the Conference of the Association of German Professors of Constitutional Law that was held in Marburg, Germany, on 9-12 October 2019.